Budaya Cethe dalam Masyarakat Tulungagung Sebagai Media Promosi Pariwisata Kabupaten Tulungagung - Widiyanto, Eri; Ridiatno, Arta; Herwanto, Mochammad Tri (SENTRI: Jurnal Riset Ilmiah, 2025)
The cethe culture is a distinctive coffee-drinking tradition originating from Tulungagung Regency in East Java, involving the practice of enjoying coffee while decorating the surface of a cigarette with coffee grounds (cethe) using simple tools such as bamboo sticks or toothpicks. Although it appears modest, this tradition carries strong social and cultural values as it serves as a medium for interaction, communication, and togetherness within the community. Unfortunately, it remains relatively unknown outside the region, despite its significant potential as a unique and authentic cultural tourism attraction. Based on this context, it is important to examine the influence of the cethe tradition on the social life of the Tulungagung community as well as its potential as a medium for regional tourism promotion. The cethe culture symbolizes the cultural identity of Tulungagung, reflecting creativity, solidarity, and a sense of belonging to local heritage. The practice of nyethe is not merely a routine of drinking coffee and smoking, but also an artistic expression and a reflection of the community’s lifestyle. With creative promotion and support from local authorities, the cethe tradition has the potential to become a distinctive tourism icon of Tulungagung, attracting both domestic and international visitors and thereby contributing to sustainable regional income and community welfare.